2021
DOI: 10.3390/ijms22052362
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Modulate Signaling Pathways in Osteogenic Differentiation of Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) have been identified in many adult tissues and they have been closely studied in recent years, especially in view of their potential use for treating diseases and damaged tissues and organs. MSCs are capable of self-replication and differentiation into osteoblasts and are considered an important source of cells in tissue engineering for bone regeneration. Several epigenetic factors are believed to play a role in the osteogenic differentiation of MSCs, including microRNAs (miRNAs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 188 publications
(233 reference statements)
2
38
0
1
Order By: Relevance
“…MicroRNAs (miRNAs) are endogenous 22-nucleotide long non-coding RNAs that regulate gene expression by binding to the 3´ untranslated region (UTR) of their target mRNAs and promoting mRNA degradation and/or inhibiting RNA translation. MiRNAs have been shown to play an important role in the osteogenic lineage commitment of MSCs by targeting the expression of transcription factors and components of the primary bone formation pathways [ 40 ]. Important differences in the expression of specific miRNAs have been found for HD-MSCs and MM-MSCs when subjected to osteogenic differentiation conditions.…”
Section: Characterization Of Mesenchymal Stromal Cells In Multiple Myelomamentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous 22-nucleotide long non-coding RNAs that regulate gene expression by binding to the 3´ untranslated region (UTR) of their target mRNAs and promoting mRNA degradation and/or inhibiting RNA translation. MiRNAs have been shown to play an important role in the osteogenic lineage commitment of MSCs by targeting the expression of transcription factors and components of the primary bone formation pathways [ 40 ]. Important differences in the expression of specific miRNAs have been found for HD-MSCs and MM-MSCs when subjected to osteogenic differentiation conditions.…”
Section: Characterization Of Mesenchymal Stromal Cells In Multiple Myelomamentioning
confidence: 99%
“…It has been reported that miRNA can regulate the osteogenic differentiation of BMSCs and PDLSCs. For BMSC, MiRNAs control gene expression in osteogenic differentiation by regulating two crucial signaling cascades in osteogenesis: the transforming growth factor-beta (TGF-β)/bone morphogenic protein (BMP) and the Wingless/Int-1(Wnt)/β- catenin signaling pathways ( Mazziotta et al, 2021 ). In previous literature, miR-17, miR-21, miR23a, miR-24, miR-132, miR-138, miR-214, miR-218, miR-543, and miR1305 have been reported to regulate PDLSCs Osteogenic differentiation ( Ahmad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is now estimated that miRNAs target approximately 60% of genes in humans and other mammals [ 42 ]. Due to their role in mRNA expression regulation, miRNAs are involved in all cellular activities, including proliferation, differentiation, migration, apoptosis, and immune responses, both in normal and pathological conditions [ 43 , 44 , 45 , 46 ]. Several mechanisms ensure high stability in miRNAs.…”
Section: Mirna Activities and Identificationmentioning
confidence: 99%
“…miRNA activity mainly induces gene expression reduction by binding to sequences in the 3′ untranslated region (3′-UTR) of target genes. This can lead to mRNA target degradation, or inhibition of translation and reduction in protein levels [ 45 ]. However, miRNA activities show higher complexity as each miRNA can target different genes and several miRNAs can regulate the same gene’s expression.…”
Section: Mirna Activities and Identificationmentioning
confidence: 99%
See 1 more Smart Citation